Usefulness of Change in Estimated Glomerular Filtration Rate as a Predicting Factor of Progression of Chronic Kidney Disease - Maeda, Kunimi (Hindawi Publishing Corporation, 2012)
Purpose. To explore factors contributing to chronic kidney disease (CKD) progression and change in estimated glomerular filtration rate over time (ΔeGFR) as a risk factor in predialysis patients under multidisciplinary managements. Methods. Among 113 CKD patients, eGFR, serum creatinine, total protein, albumin, urea nitrogen, uric acid, calcium, inorganic phosphate, total cholesterol, urinary creatinine, urinary protein (UP), hemoglobin A1c, hemoglobin, and hematocrit were analyzed. Results. ΔeGFR analysis in the first six months presented a positive slope (remission group) in 43 patients (38%) and a negative slope (no-remission group) in 70 patients (62%). Three-year dialysis-free rate was 89.4% in the remission group and 39.3% in the no-remission group, with a significant difference (P < 0.0001). To explore factors contributing to dialysis initiation by stepwise Cox regression, baseline eGFR (HR 0.706, P < 0.0001) and ΔeGFR in the first six months of treatment (HR 0.075, P < 0.0001) were identified. To investigate factors affecting remission and no remission by stepwise logistic regression, age (odds ratio 1.06, P = 0.018) and UP excretion (odds ratio 1.223, P = 0.045) were identified. Conclusion. Monitoring of ΔeGFR and UP is not only useful in suppressing CKD 3 progression, but also in deciding strategies to achieve remission in individual patients.